Industrial Waste-Water Treatment using IoT - Divya, Y.; Achiammal, B.; Sahoo, Santosh Kumar (Journal of ISMAC, 2023)
Environmental safety management has recently been the most difficult task in this rapidly urbanising country. Wastewater management is a method of treating waste that can be reused rather than thrown away. One of the most efficient ways to handle garbage is to reduce and recycle. For decades, wastewater treatment companies have been dealing with a plethora of difficulties centred on how to avoid trash being managed. Separating wastes thrown in water, such as paints and battery wastes, is difficult since they require a unique classification and recycling procedure. In Telangana, the waste developed from dairy industry requires to be treated properly for reuse of same due to scarcity of water. So, the Internet of Things (IoT) for a waste management solution is considered here to address the above concerns.. Hence, the proposed method focusses on an IoT based wastewater treatment and monitoring for smooth operation and reuse. During implementation, it was concluded with confirmation that the proposed system has high accuracy in the range of 96% as compared to other existing models.